Literature Teachers’ Views on Ecocritical Pedagogy: A Preliminary Study in Serbia - Ognjanović, Branka B.; Kandić, Milica A. (Studies in Teaching and Education, 2025)
The paper explores teachers’ perspectives on the presence and relevance of ecocritical pedagogy in literature education within Serbian elementary and secondary schools. Despite the growing global recognition of the educational potential of ecocriticism – defined as an interdisciplinary study of the relationship between literature and the environment – its application in Serbian curricula remains limited and underexamined. The study aimed to investigate potential differences across education levels (lower and upper grades of elementary school and secondary school), teaching experience, and teachers’ perceptions of the possibilities and challenges regarding the integration of ecocritical pedagogy. A mixed-methods approach was employed using both quantitative and qualitative survey data from 213 teachers. Findings indicated that teachers generally lack familiarity with ecocriticism and perceived ecocritical pedagogy, on average, as more relevant than it is currently represented in education. Statistically significant differences emerged by education levels: teachers of lower elementary grades scored highest on both presence and relevance subscales. Most teachers, however, valued the development of critical thinking as a central outcome of ecocritical pedagogy and expressed willingness to integrate it into practice. No significant differences were observed by teaching experience. The results highlight the need for structured support to bridge the gap between theoretical potential and classroom implementation, as teachers recognize literature’s capacity to contribute to holistic, interdisciplinary environmental education, encouraging critical thinking, empathy, and student engagement with contemporary, real-world issues.
Keywords: Ecocritical Pedagogy; Ecocriticism; Environmental Education; Literature Education; Teachers' Perceptions